The Effect of Disclosure of Intellectual Capital Components on the Market Price of Shares in Jordanian Industrial Companies: An Empirical Study - Ali, Osama Abdulmunium (International Journal of Economics and Financial Issues, 2018)
This study aims to identify the effect of the disclosure of intellectual capital on the market value of shares in Jordanian commercial banks by shedding light on the level of disclosure of intellectual, human, structural and relational capital on the market value of the share. The study community shall be composed of all the Jordanian industrial companies and public shares traded in the Amman Stock Exchange during the study period (2013-2016). To achieve the objectives of the study, the researcher collected secondary data through reference to previous studies, books and administrative research on the subject of disclosure, as well as specialized journals. The researcher used the statistical program (SPSS) to analyze the data. The study reached the most important results which showed that the general trend in the four years (2013-2016) was towards increasing the level of disclosure of the components of intellectual capital. This indicates the continuous increase by the industrial companies at the level of disclosure, However, this level was below the required threshold, not exceeding in all years (56.0%). There is also a relative increase in the level of disclosure of structural capital and interest relative to the disclosure of human capital, which may be seen as a decline in the interest of companies in the development of their human resources compared to the structural aspect and relations with other parties. The study recommended that companies’ managements should monitor the changes in their share prices, trading volume and how investors evaluate the company’s shares, in order to confirm the achievement of the most important objectives of financial management. Disclosure of intellectual capital components, and companies based on reference comparisons with international companies, to reach full disclosure of all items that measure the components of intellectual capital. Keywords: accounting disclosure, intellectual capital, market price per share JEL Classifications: M41, O34